Determinants of reduced cognitive performance in HIV-1-infected middle-aged men on combination antiretroviral therapy. (24th April 2016) - Schouten, Judith; Su, Tanja; Wit, Ferdinand W.; Kootstra, Neeltje A.; Caan, Matthan W.A.; Geurtsen, Gert J.; Schmand, Ben A.; Stolte, Ineke G.; Prins, Maria; Majoie, Charles B.; Portegies, Peter; Reiss, Peter
Abstract : Objective: The spectrum of risk factors for HIV-associated cognitive impairment is likely very broad and includes not only HIV/antiretroviral therapy-specific factors but also other comorbid conditions. The purpose of this current study was to explore possible determinants for decreased cognitive performance. Design and methods: Neuropsychological assessment was performed on 103 HIV-1-infected men with suppressed viraemia on combination antiretroviral therapy for at least 12 months and 74 HIV-uninfected highly similar male controls, all aged at least 45 years. Cognitive impairment and cognitive performance were determined by multivariate normative comparison (MNC). Determinants of decreased cognitive performance and cognitive impairment were investigated by linear and logistic regression analysis, respectively. Results: Cognitive impairment as diagnosed by MNC was found in 17% of HIV-1-infected men. Determinants for decreased cognitive performance by MNC as a continuous variable included cannabis use, history of prior cardiovascular disease, impaired renal function, diabetes mellitus type 2, having an above normal waist-to-hip ratio, presence of depressive symptoms, and lower nadir CD4 + cell count. Determinants for cognitive impairment, as dichotomized by MNC, included cannabis use, prior cardiovascular disease, impaired renal function, and diabetes mellitus type 2. Conclusion: Decreased cognitive performance probably results from a multifactorial process, including not only HIV-associated factors, such as having experienced more severe immune deficiency, but also cardiovascular/metabolic factors, cannabis use, and depressive symptoms.